Hurricane Gold (UK Penguin Books, 2012)
As the sun blazes over the Caribbean island of Lagrimas Negras, its bloodthirsty ruler is watching and waiting. Criminals come here to hide, with blood on their hands and escape on their minds. On the mainland, in the quiet town of Tres Hermanas, ex-flying ace Jack Stone leaves his son and daughter in the company of James Bond.